DIGITALISASI LAYANAN UMKM JASA STEAM: PELATIHAN PENGGUNAAN APLIKASI ANDROID UNTUK PEMESANAN CUCI MOBIL DAN MOTOR - Stefanus Digita Ardhiansyah; Agustian Syahputra; Andika Putra Kharisma; Muhammad Rasya Firdaus; Muhammad Fathur Rahman (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
This Community Service Program (PKM) focused on the digitalization of a steam car wash and motorcycle wash service business (UMKM) through the development and implementation of a mobile Android application for ordering and service management. FS Smart Car Wash, a small-scale steam cleaning service in Lebak Banten, faced significant operational challenges including manual booking processes, lack of real-time order tracking, inefficient customer communication, and limited data for business analytics. The program comprised three main components: (1) analysis and requirements gathering of the existing business processes; (2) development of a user-friendly Android application with features including customer registration, service booking, real-time order status tracking, payment integration, and service provider management; (3) comprehensive training of business owners and service staff on application usage and system maintenance. The application was developed using Android Studio with Firebase backend for real-time database management. Post-implementation evaluation during a 4-week pilot period demonstrated a 35% increase in customer bookings, 45% reduction in booking time, 40% improvement in customer satisfaction, and 50% increase in revenue during peak hours. The system also provided business analytics enabling data-driven decision making. Participant satisfaction survey showed 89% satisfaction with the training and system usability. This initiative demonstrates that digital transformation of micro and small businesses requires not only technology development but also comprehensive training, ongoing technical support, and understanding of specific business contexts. The developed application serves as a proof-of-concept for similar steam car wash businesses seeking to digitalize their operations.